The Use of Flash Cards Media in Reducing Speech Delay Symptoms in Children (A Case Study in BA Aisyiyah Prembun, Tambak District, Banyumas Regency) - Labib Sajawandi; Yulia Kurniati; Aji Heru Muslim; Tesa Nurul Huda (UM Purwokerto Press, 2023)
The background of this study is to describe the process of using flashcard media to reduce the symptoms of speech delay in children, implemented by class teachers in BA Aisyiyah Prembun. It was found to have a significant impact on children's speech development. This study adopted a qualitative method with a case study approach. The qualitative method is used because this study aims to discuss the factors influencing children's speech delay and how the flashcards enhance the speaking skills of children with speech delays in BA Aisyiyah Prembun. Using the qualitative research method for this is more straightforward and more effective. Data collection methods in this research included observation, interviews, and documentation. The findings indicated improved speech development in the subjects after the class teacher continuously used flash cards five times a week. Initially, the subjects had difficulty speaking. However, by the 6th month, there was a significant improvement in the child's speech. They can speak fluently and clearly after the intervention using flash cards.